2021
DOI: 10.1016/j.oneear.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Toward a definition of Essential Mountain Climate Variables

Abstract: The numerous processes implicated in the rapid and profound climate-driven changes that are underway across the world's mountains must be well monitored, understood, and-as far as possible-accurately projected. However, not only are the available environmental data upon which such activities hinge often severely limited, but interdisciplinary consensus regarding which variables should be considered observation priorities also remains elusive. Here, the concept of Essential Mountain Climate Variables (EMCVs) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 137 publications
1
30
0
Order By: Relevance
“…There is another reason that makes information about the aerosol vertical distribution in a mountainous area particularly relevant: the aerosol vertical profile and its radiative effect are considered among the possible drivers for the Elevation-Dependent Warming (EDW) (Pepin et al 2015;Thornton et al 2021). The latter is the enhanced warming currently being observed in high-altitude regions of the world with respect to the climate change observed at lower altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…There is another reason that makes information about the aerosol vertical distribution in a mountainous area particularly relevant: the aerosol vertical profile and its radiative effect are considered among the possible drivers for the Elevation-Dependent Warming (EDW) (Pepin et al 2015;Thornton et al 2021). The latter is the enhanced warming currently being observed in high-altitude regions of the world with respect to the climate change observed at lower altitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Overall and despite many recent efforts, there is still a lack of datasets for many regions. Where such datasets exist, they still have a disciplinary focus, and their fragmentation and often a lack of accessibility are major challenges (Thornton et al 2021). The question, therefore, remains whether existing datasets from high-elevation regions serve the purpose of a holistic approach to understanding environmental change in mountains and assessment of impacts and vulnerabilities.…”
Section: Thematic Gaps and Suitability Of The Available Datasetsmentioning
confidence: 99%
“…The second task is to continue the development of metrics and indicators to be monitored by mountain observatories to ensure consistency and comparability of data in collaboration with GEO Mountains and Global Climate Observing System (GCOS) programs and thematic networks. A set of Essential Climate Variables (ECVs) specific to mountain environments is being developed as an activity of GEO Mountains, with the inputs of the relevant MRI Working Groups (Thornton et al 2021). Mountain-specific ECVs are defined with respect to different mountain processes such as cryospheric change, ecological change, and the hydrological cycle, building on and complementing the existing ECVs as defined by GCOS.…”
Section: Mountain Observatories: Quo Vadis?mentioning
confidence: 99%
See 1 more Smart Citation
“…Fasano et al [38] showed that even over a pristine Alpine region, transported Saharan dust can increase atmospheric heating rates (HR) by more than 1 K/day (relative to aerosol-free atmosphere), and at the same time have a negative radiative effect at the top and at the bottom of the atmosphere. At such regions (i.e., Alpine Valleys) changes in atmospheric heating have an immediate impact on the climate of the slopes and are considered among the possible drivers for Elevation-Dependent Warming (EDW) [39,40]. Many studies show that aerosols affect the Asian monsoon water cycle.…”
Section: Introductionmentioning
confidence: 99%